Barium partitioning in calcite and aragonite as a function of growth rate. (15th September 2018) - Mavromatis, V.; Goetschl, K.E.; Grengg, C.; Konrad, F.; Purgstaller, B.; Dietzel, M.
Abstract: Calcite and aragonite growth rate experiments have been performed in the presence of aqueous Ba at 25 °C using the constant addition technique as a function of CaCO3 mineral growth rate (mol/m 2 /s). The partitioning of Ba in calcite at −8.4 ≤ Log rcalcite ≤ −7.3 exhibits a weak dependence on growth rate that can be expressed as: L o g D Ba, c a l c i t e = 0.2477 ± 0.0543 × L o g r c a l c i t e - 0.2949 ± 0.4222 ; R 2 = 0.81 In the case of aragonite, Ba partitioning at −9.0 ≤ Log raragonite ≤ −7.8, exhibits a much stronger dependence on growth rate that can be described as: L o g D Ba, a r a g o n i t e = 0.4458 ± 0.0563 × L o g r a r a g o n i t e + 3.3407 ± 0.4668 ; R 2 = 0.84 The determined DBa, aragonite values are systematically lower than unity and come in contrast to previous experimental works where Ba partitioning studied during aragonite nucleation. They are, however, in excellent agreement with the theoretical free energy correlation model by Wang and Xu (2001) that considers the effect of ionic radii size on DBa, aragonite . The defined growth rate dependence of Ba incorporation in aragonite provides new insights on the role of ionic radii size during the incorporation of trace elements and the formation of solid-solutions from aqueous solutions at low oversaturation degrees. The data presented here shed light on the process controlling the elevated DBa, aragonite values occurring at high saturation degrees of natural fluids with respect to aragonite that have been recorded in natural samples. Furthermore, the trend experimentally obtained herein has the potential to record variations in growth rate regimes in natural occurring aragonites and to provide information on the environmental conditions of natural waters in the past.